Termopotássio: fertilizante alternativo para a agricultura brasileira - Duarte, Ivaniele Nahas (2012)
In order to evaluate the use of the thermopotash as a source of potassium and other nutrients for plants, three studies were conducted: one incubation study, one leaching study and a biological study. In all studies the soils used were Ustoxic Quartzipsamment (RQo) and Oxysol Red (LVd). The first study, evaluated the release of silicon, calcium, magnesium and, mainly, potassium to the soil, as well as the corrective action, by thermopotash, Verdete and KCl. Three potassium sources (KCl, thermopotash, Verdete) and two doses of potassium (200 and 400 kg ha-1) were used in this study. The experiment lasted 60 days, and at its end, soluble Si, pH CaCl2, Ca2+ and Mg2+, and K+ were determined. It was observed that the thermopotash is a source of several nutrients and can also act as a soil corrective, unlike of Verdete. The second test evaluated leaching losses of potassium from KCl, granulated thermopotash, powder thermopotash, in samples of LVd and RQo. The three sources of potassium were distributed in 20-cm diameter and 80-cm high leaching columns. Potassium content was determined at the end of the experiment in each column ring. In both soil types, powder thermopotash supplied more potassium, in the top soil layer (0 - 20cm), while KCl supplied more potassium to lower layers. Therefore, potassium from the KCl is more prone to leaching than that from thermopotash. Soil mobility of granulated and powder thermopotash was similar. In the biological study, done in pots, millet was grown two consecutive times to determine the absorption of potassium and other nutrients, present in thermopotash and Verdete and compare it to Mehlich-1 and resin extraction to compare the results with potassium available to plants. In this test, the same treatments of the incubation study were used. At the end of experiment, dry matter, K+, Ca2+, Mg2+, Si contents in above ground millet matter, and accumulated in millet above ground matter, and potassium in soil were analyzed. For two consecutive crops, the agronomic efficiency of thermopotash was greater that KCl in samples of LVd and lower in samples of RQo. In both soil samples, millet absorbed potassium, calcium, magnesium and silicon supplied by thermopotash in the first and the second crops. The agronomic efficiency of verdete, was lower than that of KCl and thermopotash, both in LVd and RQo. Moreover, in soils fertilized with thermopotash, the best method used to determine available potassium for plants was ion exchange resin. In conclusion, thermopotash can used as potassium, calcium, magnesium and silicon sources in millet, and can correct the pH of soils.